MODERN CHALLENGES OF GLOBALIZATION AND THEIR INFLUENCE ON THE DEVELOPMENT OF KYRGYZSTAN - Seikimbaeva B. K. (Vestnik Issyk-Kulʹskogo universiteta)
Modern challenges of globalization have a significant impact on the socio-economic development of countries, including Kyrgyzstan. In an increasingly integrated global economy, the key challenges for the Kyrgyzstan are adaptation to rapid technological changes, competitive pressure on domestic markets, increased dependence on foreign trade, as well as problems of sustainable development. The issues of ecology, migration, leakage of qualified personnel and uneven economic development of regions are becoming particularly relevant. Globalization opens up new opportunities for growth and development, such as access to international markets, innovative technologies and investments. Nevertheless, Kyrgyzstan faces a number of problems related to economic vulnerability to external shocks, limited resources for industrial modernization and a low level of innovation activity. In addition, there is a growing need for effective regulation and integration into global processes, especially in the context of participation in international organizations and trade unions. The abstract of this work emphasizes the importance of studying the impact of globalization on the national economy and the need to develop strategies that will help Kyrgyzstan effectively adapt to modern challenges, minimize risks and use the opportunities of global interaction for the sustainable development of the country.